Factors influencing customer loyalty in choosing Goodhope Hotel Johor Bahru / Siti Fairuz Mohd Hatta - Mohd Hatta, Siti Fairuz (Faculty of Business and Management, 2018)
Hospitality and tourism is a key sector in the world economy today and accounts for more than a third of the total global services trade (Bharwani & Mathews D., 2012). Besides, over the past quarter of the century, international tourist arrivals have increased about one percentage point faster than global GDP in real terms. The main objective of this research was to investigate the factors that influencing customer loyalty in Goodhope Hotel Johor Bahru. The research used four independent variables which are location, cleanliness, customer service and security and safety. A convenience sampling technique was used to select a sample 220 respondents from a target population of 566 customers. Data analysis was carried out using quantitative technique with the aid of Statistical Package for Social Science (SPSS) version 20. The research found that from four independent variables assessed in the study, all of them have shown a significant relationship which is location, cleanliness, customer service and security and safety towards customer loyalty in choosing Goodhope Hotel Johor Bahru.